Insights into the Functions of M-T Hook Structure in HIV Fusion Inhibitor Using Molecular Modeling. (April 2016) - Tan, Jianjun; Yuan, Hongling; Li, Chunhua; Zhang, Xiaoyi; Wang, Cunxin
Graphical abstract: The binding model of the gp41 with the ligand. The structural composites from the average structure of the 20–50 ns molecular dynamic simulations trajectories. Highlights: We explored the mechanism why M-T could improve the activity of inhibitors. The system with the M-T hook structure formed more stable hydrogen bonds than without M-T hook structure. The M-T hook could further fortify the interaction by "hooking" the pocket residues tightly; in contrast, this structure do not appear in the system without the M-T hook. Binding free energy of the ligand with M-T was higher than the other without M-T. Abstract: HIV-1 membrane fusion plays an important role in the process that HIV-1 entries host cells. As a treatment strategy targeting HIV-1 entry process, fusion inhibitors have been proposed. Nevertheless, development of a short peptide possessing high anti-HIV potency is considered a daunting challenge. He et al. found that two residues, Met626 and Thr627, located the upstream of the C-terminal heptad repeat of the gp41, formed a unique hook-like structure (M-T hook) that can dramatically improve the binding stability and anti-HIV activity of the inhibitors. In this work, we explored the molecular mechanism why M-T hook structure could improve the anti-HIV activity of inhibitors. Firstly, molecular dynamic simulation was used to obtain information on the time evolution between gp41 and ligands. Secondly, based on the simulations, molecular mechanics Poisson–Boltzmann surface area (MM-PBSA) and molecular mechanics Generalized Born surface area (MM-GBSA) methods were used to calculate the binding free energies. The binding free energy of the ligand with M-T hook was considerably higher than the other without M-T. Further studies showed that the hydrophobic interactions made the dominant contribution to the binding free energy. The numbers of Hydrogen bonds between gp41 and the ligand with M-T hook structure were more than the other. These findings should provide insights into the inhibition mechanism of the short peptide fusion inhibitors and be useful for the rational design of novel fusion inhibitors in the future.